The way of future through voluntary selection - Omid Sadeghi Fathabadi (Global Journal of Ecology - Peertechz Publications, 2023)
This article is a follow-up on the recent publication introducing the concept of "Voluntary Selection" which allows for engineering the phenotypic profile of a population by adopting the reproductive cells of donors rather than couples themselves. Foreseeing a genetically converging world through Voluntary Selection, and looking from a Middle Eastern and North African perspective, the article focuses on five major themes where improvements are necessary to allow for maintaining stability and achieving a minimum level of living standards despite matters such as different levels of access to environmental resources, global warming and depleting fossil fuel resources. These themes are namely the provision of evolutionary explanation for religions, women's rights, generating wealth in the form of living atmospheres, distributed workload across society and distributed food production. The following discussions illustrate how by changing the way we look at the world, utilizing our available but neglected resources, dreaming, believing, and acting, we can solve some of the most fundamental global problems. The provided solutions are protective of individual freedoms, facilitate the convergence of lifestyles to a pleasant, practical, elegant, sustainable and modern model and protect the fabric of society as the foundation for higher-level achievements necessary for the maintenance and improvement of our living standards.